2016
DOI: 10.1007/s10646-016-1671-5
|View full text |Cite
|
Sign up to set email alerts
|

Trait modality distribution of aquatic macrofauna communities as explained by pesticides and water chemistry

Abstract: Analyzing functional species’ characteristics (species traits) that represent physiological, life history and morphological characteristics of species help understanding the impacts of various stressors on aquatic communities at field conditions. This research aimed to study the combined effects of pesticides and other environmental factors (temperature, dissolved oxygen, dissolved organic carbon, floating macrophytes cover, phosphate, nitrite, and nitrate) on the trait modality distribution of aquatic macrofa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
1
7
2
1
Order By: Relevance
“…Shahid et al, 2018), and so the loss of intolerant species would not result in a decrease in family richness. This explanation was also suggested by Ieromina et al (2016), who describe an intriguingly similar result to ours: a nutrient (phosphate) was the most important predictor structuring invertebrate communities, assessed by the composition of functional traits, in agricultural ditches, while pesticides had no effect. They speculated that communities may adapt to pesticide stress through sensitive species being replaced by tolerant ones with similar functional traits, thus maintaining community trait composition.…”
Section: Discussionsupporting
confidence: 89%
“…Shahid et al, 2018), and so the loss of intolerant species would not result in a decrease in family richness. This explanation was also suggested by Ieromina et al (2016), who describe an intriguingly similar result to ours: a nutrient (phosphate) was the most important predictor structuring invertebrate communities, assessed by the composition of functional traits, in agricultural ditches, while pesticides had no effect. They speculated that communities may adapt to pesticide stress through sensitive species being replaced by tolerant ones with similar functional traits, thus maintaining community trait composition.…”
Section: Discussionsupporting
confidence: 89%
“…The widespread use of bioindicators for assessing the ecological situation of waterbodies rests in the fact that the structure of biological communities is a function of the influence of the whole spectrum of natural and anthropogenic factors, with the bioindicators providing an integral response to this situation. The effectiveness of the bioindication method in environmental studies has been reported by a number of researchers (Ieromina, Musters, Bodegom, Peijnenburg, & Vijver, ; Ochocka & Pasztaleniec, ; Rocha, Andrade, & Lopes, ; Svensson, Bellamy, Van den Brink, Tedengren, & Gunnarsson, ).…”
Section: Introductionmentioning
confidence: 94%
“…Dit omdat de verhoogde nutriëntengehaltes ervoor zorgen dat aquatische ecosystemen van een heldere, door waterplanten gedomineerde situatie omslaan naar een troebele door algen gedomineerde situatie waarin een andere, soortenarmere insectengemeenschap voorkomt (Scheffer 1998). Zo correleerde de fosfaatbelasting van verschillende Nederlandse waterlichamen met aquatische levensgemeenschappen waarbij minder soorten met een diapause/winterrust of popstadium voorkwamen en meer soorten met een parasitaire levenswijze aanwezig waren dan in gemeenschappen waar de fosfaatbelasting lager was (Ieromina, Musters et al 2016 (Hanski, 1998;Ovaskainen and Hanski, 2003;Hanski, Schulz et al 2017). In het algemeen geldt dat insectensoorten met een lange levensduur en een geringe dispersiecapaciteit gevoeliger zijn voor de negatieve effecten van versnippering (Vermeulen, 1995;Hanski, 1998;Wallis de Vries, 2014;Van Noordwijk, Verberk et al 2015;Rossetti, Tscharntke et al 2017).…”
Section: Effecten Van Stikstof En Fosfaat In Aquatische Ecosystemenunclassified